PENDIDIKAN KARAKTER DALAM SURAT LUQMAN AYAT 13-14 - Faza Ilya; Awal Nur Ramadhan; Ana Rahmawati (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
The study aims to explain the Character Education Method in Surah Luqman Verses 13 & 14. In Surah Luqman verses 13-14, Allah SWT provides guidance on character education, which Luqman taught his son. Verse 13 emphasizes the oneness of Allah (tawhid) and a warning to avoid shirk, which is the main basis of morality in Islam. This message is important for forming a child's understanding of God as the main foundation of moral values. Meanwhile, verse 14 emphasizes the obligation to serve parents as part of noble morals. Through this obligation, children are expected to grow up with an attitude of respect and gratitude, especially for the sacrifices of mothers who care for them from the womb to breastfeeding. Several studies have explored the method of character education taken from this verse. For example, Zubaedy (2018) in the journal Didaktika states that character education that begins with strengthening tawhid and obedience to parents is an important pillar for instilling morals in the younger generation. Interpretations from scholars also support this approach, highlighting that strengthening faith and affection in the family is the foundation for forming a society with strong character. Character education from the perspective of the Qur'an, especially in Surah Luqman verses 13-14, includes two main pillars: tawhid (the oneness of Allah) and respect for parents. Maulana explains that character education based on tawhid forms the basis of ethics and morality for children, because tawhid instills the awareness that all human actions must be based on submission to Allah. This strengthens moral integrity and personal responsibility which are important in character education. Maulana (2020) in his article in the Jurnal Akhlak Mulia. In addition, respect and obedience to parents taught in verse 14 serve as the foundation for social morals. Maulana highlights that the value of devotion to parents reflects the concept of gratitude and appreciation for sacrifice, which is not only important in family life but also relevant to creating a generation that values the values of togetherness and empathy. Maulana also notes that the implementation of this teaching can build children's character based on compassion, respect, and social responsibility.